Refugee Children’s Access to Play in Meso-Environments: A Novel Approach Using Space Syntax and GIS - Chen, Siqi; Knöll, Martin (Buildings (Basel), 2023)
Being able to explore and play in quality open spaces in the neighbourhood is crucial for refugee children since refugee facilities often have inadequate playspaces indoors and outdoors. Access to meso-environment playspaces (around refugee accommodations) would provide refugee children with the opportunity for optimal physical, cognitive, emotional and social development and support their social inclusion. This study explores refugee children’s access to play areas in meso environments with six study sites in Berlin. Active space for refugee children’s play is assessed using: (1) open-source data collection, (2) method notions of perceived distance and spaces, (3) staff survey with site investigation and (4) space syntax theories of potential accessibility. Results indicated the fact of unequal playspace distributions for refugee children in Berlin with children-oriented assessment. The utilisation of space syntax in the context of refugee children is relatively unexplored. This study is thereby contributing to the space syntax literature by exploring the broader application potential of its methods. Further studies should broaden study sites with more precise environmental measures.